2016
DOI: 10.1093/cid/ciw189
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up of Patients With Lyme Disease: Longitudinal Analysis of Clinical and Quality-of-life Measures

Abstract: NCT00028080.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 34 publications
3
18
0
2
Order By: Relevance
“…The results of this study correspond quite well with the results of a recent US study on QoL among LB patients, in which EM patients had better QoL-scores than other LB patients, and lower QoL scores were associated with comorbidities [43]. …”
Section: Discussionsupporting
confidence: 88%
“…The results of this study correspond quite well with the results of a recent US study on QoL among LB patients, in which EM patients had better QoL-scores than other LB patients, and lower QoL scores were associated with comorbidities [43]. …”
Section: Discussionsupporting
confidence: 88%
“…More severe disease at onset in the form of a higher number of symptoms (37) and/or objective signs (such as Bell's Palsy) or symptoms (such as headache, photophobia, or neck pain) which suggest dissemination to the nervous system may be present and may increase the risk of persistent symptoms following treatment (33,38). One recent study has shown that the presence of pre-existing co-morbidities in Lyme disease was predictive of long-term symptoms and lower quality of life (39), similar to other disease settings (40,41). Delays in diagnosis and initiation of appropriate treatment, which importantly may be driven by patient health insurance status (42), have also been shown to increase risk (31,32).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Currently, there are no commonly agreed-upon symptoms, laboratory, or imaging findings which are sensitive and specific to aid in the clinical evaluation of patients with persistent symptoms in Lyme disease. Therefore, the clinical diagnosis is primarily one of exclusion, and the current illness must be distinguished both from other systemic inflammatory, rheumatic, malignant and infectious conditions, as well as the effects of co-morbid or pre-existing conditions (39). This raises the possibility of anchoring bias, or the misattribution of either symptoms or positive serologies in low-endemic areas to prior Lyme disease, when in fact the symptoms are caused by a new, unrelated illness (67,68).…”
Section: Clinical Presentationsmentioning
confidence: 99%
“…Second, immunogenetic mechanisms have been proposed, but prospective observational studies on dysregulated immune responses161162163 and case-control studies on autoimmune processes164165 have been inconclusive. Third, associations of PTDLS have been described with demographic, clinical, and epidemiological patient characteristics, such as advanced age, female sex,166167 comorbidity, and duration of pre-treatment symptoms 168169. Finally, cognitive behavioral characteristics, including depression, anxiety, negative affect, and catastrophizing have been associated with the risk of developing persistent symptoms 170…”
Section: Chronic Symptoms Attributed To Lyme Borreliosismentioning
confidence: 99%